Dispersed‐Phase Holdup and Characteristic Velocity in an Agitated‐Pulsed Solvent Extraction Column. Issue 4 (16th February 2021) - Tan, Boren; Li, Longxiang; Lan, Minle; Wang, Yong; Qi, Tao
Abstract: The agitated‐pulsed column (APC) is expected to exhibit good transfer. The dispersed‐phase holdup and characteristic velocity were measured using a 25‐mm diameter APC. The holdup declined at first and then escalated with the increase of pulsation intensity which was in contrary to the trend of the characteristic velocity change. The pulsation intensity corresponding to minimum holdup was found, and it increased with higher agitation speed. The interfacial area was also calculated. Correlations were developed for the holdup and characteristic velocity prediction within 5.34 % and 9.54 % deviation, respectively. Flooding lines were calculated by the characteristic velocity method and operating regimes were determined by the experimental results. Abstract : Dispersed‐phase holdup and characteristic velocity in an agitated‐pulsed solvent extraction column were measured. New correlations were developed to predict the dispersed‐phase holdup and characteristic velocity under both pulsation and agitation conditions. The flooding velocities of the agitated‐pulsed solvent extraction column can be predicted satisfactorily by characteristic velocity approach.